AN ANALYTICAL STUDY OF THE REALITY OF THE LABOR MARKET AND UNEMPLOYMENT IN IRAQ FOR THE PERIOD 2003-2013 - Haitham Sahi Jadaan , Dr.Bouabid Anis (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
objectives : Determine the reasons behind the aggravation of the phenomenon of unemployment in Iraq. Determining the economic and social consequences of the spread of unemployment. Determine the mechanism by which the unemployment phenomenon can be addressed and linked to the Iraqi labor market potential.conclusions : Iraq suffers from the phenomenon of structural unemployment resulting from the imbalance in the productive structure due to the stoppage of the main production sectors, especially the agricultural sector, industry and most agricultural activities. Privatization operations contributed to the increase in unemployment rates due to the layoffs of a large number of employees by the new investors, due to lack of experience and lack of qualifications among workers, and this led to an increase in the supply in the labor market.Recommendations :Diversifying the Iraqi economy and moving away from relying on oil as a major economic resource, developing agriculture and industry, and upgrading the infrastructure is sufficient to reduce unemployment in Iraq. It requires attention in the labor market and creating a balance between educational outcomes after preparing them, training them and obtaining qualifications with the demand for work in the Iraqi market.The recovery of investment and the development of a financial and monetary policy to support the Iraqi economy and increase the volume of employment of the Iraqi workforce in order to obtain real entry into the labor market that reduces unemployment.